Power Capacity Assessment of Hybrid Diesel-Solar Photovoltaic Microgrid in Tablas Island, Romblon - Junrey Garcia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The energy profile of Tablas Island has been demanding in the past years due to the emerging commercialization and even industrialization. Power capacity assessment was conducted in order to verify the sufficiency of power for supply in the coming years considering the increasing demand of energy. A forecast for annual power peak demand was considered in this study in comparison to the dependable capacity of the hybrid microgrid. It shows that the power peak demand from 2018 to 2030 is significantly increasing from 7.19MW to 13.02MW. The 8.8Mega-Watt (MW) diesel-fired power plant has dependable capacity of 6.16MW to 7.04MW from its 70% to 80% plant utilization respectively. The 7.5MW peak solar PV power plant has the maximum AC power capacity of 5.77MW. These power plants were the composition of the hybrid microgrid delivering power from 6.80MW to 8.89MW. Based on the forecast data for annual power peak demand towards 2030, it only met the demand of 8.65MW in the year 2021 but this power did not meet the peak demand in the succeeding years. Several methods to augment the power capacity of the hybrid microgrid were suggested in this study considering the mixed application of conventional and the application of more renewable energy sources as power key-players for generation and distribution.